2015
DOI: 10.1097/sla.0000000000000580
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells in Patients With Colorectal Liver Metastasis Predict Impaired Survival

Abstract: CTCs predict nonresectability and impaired survival. CTC analysis should be considered as a tool for decision-making before liver resection in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 25 publications
2
35
1
Order By: Relevance
“…30 Perhaps more surprisingly is what features were not prognostic. None of the clinical factors used in known [12][13][14][16][17][18][19][20][21][22] In addition, we did not validate neutrophil-to-lymphocyte ratio above 5 as associated with outcomes, although this has been shown in separate series. 31,32 Measurement of HV CTCs preoperatively by central venous catheterization is feasible but invasive and impractical for a single blood draw.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…30 Perhaps more surprisingly is what features were not prognostic. None of the clinical factors used in known [12][13][14][16][17][18][19][20][21][22] In addition, we did not validate neutrophil-to-lymphocyte ratio above 5 as associated with outcomes, although this has been shown in separate series. 31,32 Measurement of HV CTCs preoperatively by central venous catheterization is feasible but invasive and impractical for a single blood draw.…”
Section: Discussioncontrasting
confidence: 49%
“…5,6 In this same context of resectable CRLMs, five studies have characterized CTCs in PV using either PCR-based or cell-surface-based techniques in small sample sizes, with mixed results. 12,16,19,22,23 A meta-analysis of all studies on circulating and disseminated tumor cells in patients with metastatic CRC reported that elevated levels by any measure were associated with worse outcomes for the palliative and curative intent groups combined, but the hazard ratios were not significant in the resectable subgroup alone, which was composed exclusively of CRLM cases. 10 The lack of consensus in these studies supports our finding that PV CTCs are not likely prognostic as a strong effect size would likely have been validated previously.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Inclusion criteria were patients with histopathologically confirmed colorectal cancer and suspected synchronous or metachronous CRLM who were referred for liver resection at our institution. The CRLM had to be preliminary considered resectable, defined as feasible R0 or R1-resection (resection of all CRLM with macroscopic tumor-free resection margins) with a sufficient liver remnant [14][15][16]. A multidisciplinary team including liversurgeons, oncologists and radiologists determined a preliminary treatment-strategy and resectability based on clinical information and CT findings in portal venous phase from the referring institutions.…”
Section: Methodsmentioning
confidence: 99%
“…Biopsy of each individual metastasis is not practical, safe, nor particularly cost-effective. In recent years, there has been a resurrection of the notion to do a 'liquid biopsy,' which essentially involves sampling of circulating tumor cells (CTC) and/or cell free nucleic acids (cfDNA, including microRNA (miRNA)) present in blood and lymph [12][13][14][15][16].…”
mentioning
confidence: 99%